Hubungan Asupan Makanan Berisiko Dan Aktivitas Fisik Dengan Kejadian Diabetes Melitus Tipe II Di Kota Kupang - Maria Sambriong (JURNAL INFO KESEHATAN, 2018)
Diabetes mellitus (DM) is a serious threat to health development and ranked 6th as a cause of death. About 1.3 million people die from diabetes and 4% die before age 70 (Infodatin, 2014). In the province of East Nusa Tenggara, this disease ranks 19th has increased to 3 times compared to 2007. Cases of diabetes mellitus in the city of Kupang vary greatly in each age group wherein 2014 the proportion of the highest cases was at age 65-75 years totaling 780 people (Kupang City Health Profile, 2014). High energy intake from pure carbohydrates will stimulate insulin secretion by pancreatic beta cells as compensation to increase blood sugar levels. At a certain level, compensation efforts will not be able to compensate for insulin resistance so insulin insufficiency will arise with glucose intolerance (Waspadji et al., 2003). Polikandrioti and Dokoutsidou (2009), said obesity and lack of physical activity are also directly closely related to insulin resistance as is the characteristic of type 2 diabetes mellitus. This study was to analyze the relationship between risky food intake and physical activity with the incidence of type 2 diabetes mellitus. observational study with a case-control design. The population is 52,965 people living in the city of Kupang. The total number of samples was 234 people who met the inclusion criteria, consisting of 117 cases of type 2 diabetes and control group of 117 people who did not have type 2 diabetes mellitus taken in 2 stages: the first stage was to determine the cluster of research areas, and second consecutive sampling was taken. The measuring instrument used is the questionnaire International Physical Activity Activity Test (IPAQ), format Food Recall 24 hours and semi Quantitative Food Frequency Questioner (FFQ), Food Model, Waist ruler/tape measure. Data were analyzed using a Chi-Square test to see the relationship between; food intake is at risk with visceral obesity, visceral obesity with type 2 diabetes mellitus, food intake at risk with type 2 diabetes mellitus. To see the relationship between body activity with visceral obesity and body activity with the incidence of type 2 diabetes mellitus using Pearson Chi-Square. The results of an analysis of the bivariate energy intake test for the incidence of type 2 diabetes mellitus, had an OR of 2.543 with 95% CI = 1.4-4.3 and (p-value 0.001). Fat intake for type 2 diabetes mellitus has an OR of 1.530 with 95% CI = 0.9-2.5 and (p-value 0.142). Fiber intake for type 2 diabetes mellitus has OR 0.760 with 95% CI = 0.4-1.2 and (p-value 0.370). Visceral obesity in the incidence of type 2 diabetes mellitus has an OR 2.510 with 95% CI = 1.4-4.2 and (p-value 0.001). Energy intake for the incidence of visceral obesity has OR 28,292 with 95% CI = 13,3-59,8 and (p-value 0,000). Fat intake for the incidence of visceral obesity had OR 23.435 with 95% CI 11.4-47, 8 and (p-value 0.000). Fiber intake on the incidence of visceral obesity has OR 4.959 with 95% CI = 2.7-8.8) and (p-value 0,000). In the case group, the results of statistical tests of activity on visceral obesity found a p-value of 0.246 which means that physical activity was not associated with the incidence of visceral obesity. While the control group statistical test results obtained p-value 0.000 means that there is a relationship between physical activity and the incidence of type 2 diabetes mellitus.